2016
DOI: 10.1515/irsr-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Social network dynamics in the course of family formation: Results from a mixed-methods longitudinal study

Abstract: Abstract:In this article we examine the relationship between various biographical transitions of young adulthood and the structure of social networks. We ask how personal networks change in size and composition over the course of family formation or expansion, and due to other biographical transitions. We use data from an exploratory longitudinal study that uses mixed methods of social network analysis. We were able to reconnect with 29 of 98 young adults who were interviewed from 2004 to 2006, and conducted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The need to belong or an affiliation motive differs in strength between people and can be satisfied in different kinds of relationships such as family relationships or friendships (see Baumeister & Leary, 1995; McClelland, 1986). People are limited in their time and energy, which makes relationships often interdependent (Fiori et al, 2017; Klärner et al, 2016; Rözer et al, 2016). That is, spending time on and maintaining certain relationships usually leads to having less time and energy for other relationships.…”
Section: Friends-family-interdependencementioning
confidence: 99%
“…The need to belong or an affiliation motive differs in strength between people and can be satisfied in different kinds of relationships such as family relationships or friendships (see Baumeister & Leary, 1995; McClelland, 1986). People are limited in their time and energy, which makes relationships often interdependent (Fiori et al, 2017; Klärner et al, 2016; Rözer et al, 2016). That is, spending time on and maintaining certain relationships usually leads to having less time and energy for other relationships.…”
Section: Friends-family-interdependencementioning
confidence: 99%
“…Parenting duties continue to disproportionately fall to women (Umberson, Pudrovska, and Reczek 2010), affecting women’s daily lives and networks more strongly. New parents often experience an initial reduction in the size of their ego networks (Bost et al 2002), but this rebounds as they are soon drawn into local networks through their children’s activities, typically with residentially proximate parents of similarly aged children (Klärner, Keim, and der Lippe 2016). Friendships formed in child-centered settings may be similar in homophily for both the parents and their children, but this can be quite different from the structurally induced homophily the parents experienced in their childhoods.…”
Section: The Structure Of Opportunities For Friendship and Homophily mentioning
confidence: 99%
“…Research on heterosexual parents has demonstrated that social networks tend to change during the transition to parenthood, as individuals often spend more time with and befriend other parents (Cronenwett, 1985; Klärner, Keim, & von der Lippe, 2016). Many mothers seek out online parenting bulletin boards, playgroups, and a variety of online and in-person interactions to gain emotional and instrumental support, community, and companionship, often in response to feelings of isolation (Drentea & Moren-Cross, 2005; Hancock, Cunningham, Lawrence, Zarb, & Zubrick, 2015; Mauthner, 1995).…”
Section: Mothers’ Social Network During the Transition To Parenthoodmentioning
confidence: 99%